‘Heartware’ for the Compassionate Teacher: Humanizing the academy through mindsight, attentive love, and storytelling (Journal of Applied Learning and Teaching, 2022)
To counter the implications of fast academia, recent discourse has conceptualized the slow movement as a catalyst for humanizing the academy. Concurrently, there have been increased advocacy for pedagogical kindness within educational settings. This paper focuses on the human(e) elements of learning and teaching, such as empathy, kindness, and compassion. Whilst emphasis in educational discourse have frequently been placed on the hardware and software of teaching and learning practice, the focus on the virtues of ‘heartware’ and compassion have been limited. Specifically, there has been no study in which the thematic dimensions of: (1) mindsight and mindfulness, (2) attentive love and pedagogical kindness, and (3) storytelling in education is amalgamated to support learning. Within this context, the compassionate teacher aims to not only inspire learning journeys that are positive, engaging and fulfilling, but to also foster learning environments that are more equitable, supportive, and conducive for learners of all capabilities. This paper is conceptual in nature and proposes an approach to humanize the academy through the coaction of mindsight, attentive love, and the teacher storyteller. A conceptual framework illustrating the human(e) dimensions of ‘heartware’ for the compassionate teacher is also proposed.